Study of Basilar Artery Using Magnetic Resonance Imaging Angiography - Melani Rajendran, M. Haripriya* and S. (Recent Research in Science and Technology, 2011)
Basilar artery variations were studied in fifty patients using Three Dimensional Time of Flight Magnetic Resonance Imaging Angiography.Two basilar arteries showed variations and others found to be normal. In one case,the basilar artery showed stenosis and another case showed bulbosity. With the literature analysis, it was concluded that Magnetic Resonance Imaging Angiography is the best tool to show the anastomotic variations of the arteries of the brain and the most powerful non-invasive method for a reliable judgement for determining the degree of stenosis or any other pathology of vertebral-basilar system because it does not have the high morbidity associated with conventional intra-arterial angiography.